Editorial: Improving the return on investment in healthcare by applying Lean Management and Six Sigma principles. (9th December 2008) - Mayer, Thom; Jensen, Kirk
This editorial provides an overview of how this special issue sheds very important light on how we might begin to develop answers regarding how to improve quality, decrease costs, improve service, therefore increasing the ROI on our healthcare expenditures. Perhaps more important, the studies comprising this issue attempt not only to provide answers, but to dial up the specificity and applicability of those answers to this question: can the principles of six sigma and lean management be used to improve quality, reduce cost, improve service, and increase ROI in healthcare?